FRAME routing with game theory optimization for wireless networks. (21st November 2019) - Radha, Subramanyam; Bala, Gnanadhas Josemin; Nagabushanam, Perattur
Summary: Wireless ad hoc networks have a wide variety of applications in the present world. Creating routes between the nodes and with low energy consumption is a major challenge in wireless ad hoc networks. In this paper, we have proposed FRAME routing for ad hoc networks, which consider the entire network based on hierarchal Bayesian model. It works on game theory–based Chow‐Liu algorithm for establishing routes from source to destination considering the best neighbors in the path. FRAME routing is further analyzed with SMAC and conventional MAC in various scenarios. They are also compared with conventional MAC in AODV routing in terms of energy consumption, delay, throughput, PDR, and goodput. The entire simulations are carried out using NS2 and SMAC in FRAME routing that give better performance compared with conventional MAC in FRAME, AODV routing. Abstract :